2003
DOI: 10.4319/lo.2003.48.3.1088
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis and the dimethylsulfide (DMS) summer paradox in the Sargasso Sea

Abstract: Apparent quantum yields and rates of dimethylsulfide (DMS) photolysis were determined from Sargasso Sea seawater with the goal of assessing the extent to which photoreactions affect the unusually elevated upper ocean concentrations of DMS during the summer, the so-called DMS summer paradox. Apparent quantum yields determined with monochromatic radiation decrease exponentially with increasing wavelength and indicate that DMS photolysis is driven by ultraviolet (UV) radiation. The relative spectral partitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
130
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 48 publications
(79 reference statements)
11
130
0
Order By: Relevance
“…Downward irradiance was converted to scalar using a constant factor of 1.2 [30] and an average daily surface reflectance of 4 % was assumed. [31] When the integrated daily surface irradiance was not available for the sample day, the average daily surface irradiance for the cruise was used.…”
Section: Rate Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downward irradiance was converted to scalar using a constant factor of 1.2 [30] and an average daily surface reflectance of 4 % was assumed. [31] When the integrated daily surface irradiance was not available for the sample day, the average daily surface irradiance for the cruise was used.…”
Section: Rate Measurementsmentioning
confidence: 99%
“…Although UV-A (320-400 nm) radiation is the primary contributor to DMS photolysis, UV-B (280-320 nm) contributes 20-30 % to total photolysis with peak photolysis rates occurring at 320 nm. [30] As the SPMR and SMSR sensors do not capture UV-B wavelengths, DMS photolysis rates with depth were determined using the integrated daily UV-A dose (324-412 nm) calculated from surface irradiance data and the 324 nm attenuation depth profile (K d (l 324 )). We acknowledge that not accounting for UV-B wavelengths will result in an underestimate of photolysis rates and a slightly deeper profile.…”
Section: Rate Measurementsmentioning
confidence: 99%
“…Scaling to underwater irradiance appears justified given that water column DMS photo-oxidation was previously found to be dominated by UV-A wavelengths (Toole et al, 2003;Deal et al, 2005;Taalba et al, 2013). Estimating K d,350 from CDOM absorbance introduces some additional uncertainty, although previous work by Farmer et al (1993) in the Orinoco River plume found generally good agreement between K d,350 predicted from equation (6) and direct observations.…”
Section: Photochemical Dms Turnover and Dmso Productionmentioning
confidence: 91%
“…Previous studies reported a variable contribution from DMS photo-oxidation to overall DMS removal of around 6e70% (Kieber et al, 1996;Archer et al, 2002;Toole et al, 2003Toole et al, , 2004Bouillon et al, 2006;Simo, 2010, 2015), and indicated that photooxidation can typically dominate over losses through biological consumption and air-sea gas exchange during periods of strong stratification with shallow mixed layer depths (Toole et al, 2006;Galí and Simo, 2010). However, a recent meta-analysis of DMS cycling rates suggest that the combined contributions of photochemical and air-sea gas exchange losses generally fall below 20% (Galí and Simo, 2015).…”
Section: Photochemical Dms Turnover and Dmso Productionmentioning
confidence: 99%
See 1 more Smart Citation